Development Of Smart Dustbin By Using Apps - Jamil Alsayaydeh, Jamil Abedalrahim; Khang, Adam Wong Yoon; Indra, Win Adiyansyah; Jayasundar, Jayananthinii; Shkarupylo, Vadym (Asian Research Publishing Network, 2019)
This paper entitled Development of Smart Dustbin by Using Apps. Arduino as a controller between ultrasonic sensors, buzzer, led, fan and WiFi Module. This system implemented so that cleaning department management or cleaners can be aware with the overflow of rubbish of a dustbin at certain place. It is very useful in daily life and important for all level of people either young, old, disable people or anyone who using the dustbin to throw rubbish. This is a very important system to be implemented mainly at the indoor buildings such as supermarket. The project started to work when there is a people coming near to the dustbin to throw rubbish where it will be detected by the ultrasonic sensor and motor will be open the cover of the dustbin. The level of rubbish inside can be seen through the Blynk Apps. Once the level of rubbish reached a certain level a reminder notification will be send to the cleaning department to give a warning that dustbin going to be full. Another notification will be send once the level of rubbish reached maximum level to take immediate action to collect the rubbish through the Bylnk Apps and buzzer started to give beep sound.